2008
DOI: 10.1021/ma702408h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Properties, and Tunable Supramolecular Architecture of Regioregular Poly(3-alkylthiophene)s with Alternating Alkyl and Semifluoroalkyl Substituents

Abstract: A series of regioregular poly(3-alkylthiophene)s, Rg(Th- m,n/p ) (m = 5, 8, 11; n = 4; p = 4, 8, 12), with alternating alkyl and semifluoroalkyl substituents has been synthesized by the GRIM polymerization method. Compared with their regiorandom analogues, Rn(Th- m,n/p ), the regioregular analogues exhibit a red shift in electronic transitions in both solution and the solid state as well as considerably higher melting and crystallization temperatures. Increasing the length of alkyl side chains decreases the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 73 publications
3
62
0
1
Order By: Relevance
“…3-Dodecylthiophene (4) and its boronic acid ester (5) were synthesized as reported previously. [20,21] tallization. This yield is similar with coupling reaction starting with 2-bromo-3-semifluoroalkyl-thiophenes with longer spacers between the fluoroalkyl chains and thiothene, [20] which indicates that the short ethylene spacer does not affect the reactivity of the coupling with 5.…”
Section: Synthesis Of Bithiophene Monomermentioning
confidence: 99%
See 3 more Smart Citations
“…3-Dodecylthiophene (4) and its boronic acid ester (5) were synthesized as reported previously. [20,21] tallization. This yield is similar with coupling reaction starting with 2-bromo-3-semifluoroalkyl-thiophenes with longer spacers between the fluoroalkyl chains and thiothene, [20] which indicates that the short ethylene spacer does not affect the reactivity of the coupling with 5.…”
Section: Synthesis Of Bithiophene Monomermentioning
confidence: 99%
“…[ 20] Polymerizations P3DDFT was synthesized from the monomer 7 via the Grignard metathesis (GRIM) reaction with subsequent Nicatalyzed polymerization, which has been used to polymerize a variety of substituted 2, 2 0 -bithiophenes. [5,6,13] It has been reported that bromine-metal exchange exclusively takes place at the 5-position of the bithiophene ring, leading to the formation of regioregular P3HTs, [20] owing to steric and electronic effects.…”
Section: Synthesis Of Bithiophene Monomermentioning
confidence: 99%
See 2 more Smart Citations
“…4 Also they can be applied as platform for highly sensitive chem-and bio-detection. 5 To improve the optoelectronic properties and to realize the special applications, chemical modifications have been well performed, 6 one of which is the introduction of substituents with functional groups. 7 The design and synthesis of new conjugated polymers with special functional substituents are highly desirable.…”
Section: Introductionmentioning
confidence: 99%